2020
DOI: 10.3390/nu12072098
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Deficiency Is Associated with Mortality Risk from COVID-19

Abstract: SARS-CoV-2 infections underlie the current coronavirus disease (COVID-19) pandemic and are causative for a high death toll particularly among elderly subjects and those with comorbidities. Selenium (Se) is an essential trace element of high importance for human health and particularly for a well-balanced immune response. The mortality risk from a severe disease like sepsis or polytrauma is inversely related to Se status. We hypothesized that this relation also applies to COVID-19. Serum samples (n = 166) from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
239
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(263 citation statements)
references
References 48 publications
(72 reference statements)
14
239
0
10
Order By: Relevance
“…In the first part, we reviewed the current evidence on how RNA virus can mutate, replicate and become more virulent in Se-deficient environment. There is now evidence that SARS-CoV-2 behaves similarly with the recent study from Zhang et al (28) showing the link between COVID-19 recovery rate and the Se population status in 17 Chinese cities and Moghaddam et al pointing at a strong correlation with low Se status and poor outcome in hospitalized patients (29) It is also important to note that SARS-Cov-2 Spike Protein S mutated (D614G) leading to an apparently more infectious strain now dominant in the Western regions as in the US (113,114). Se presents various potential interests that can be applied to COVID-19 (115,116).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In the first part, we reviewed the current evidence on how RNA virus can mutate, replicate and become more virulent in Se-deficient environment. There is now evidence that SARS-CoV-2 behaves similarly with the recent study from Zhang et al (28) showing the link between COVID-19 recovery rate and the Se population status in 17 Chinese cities and Moghaddam et al pointing at a strong correlation with low Se status and poor outcome in hospitalized patients (29) It is also important to note that SARS-Cov-2 Spike Protein S mutated (D614G) leading to an apparently more infectious strain now dominant in the Western regions as in the US (113,114). Se presents various potential interests that can be applied to COVID-19 (115,116).…”
Section: Discussionsupporting
confidence: 64%
“…This observation, like the Hou's study cited above for epidemic hemorrhagic fever (16), goes against the conventional wisdom that there is no benefit in Se supplementation above the minimum required dietary intake. These population based data have been recently confirmed in clinical practice in a study by Moghaddam et al in Germany (29). They showed that serum Se levels were highly correlated with COVID-19 outcome in hospitalized patients.…”
Section: Coronavirus Sars-cov-2mentioning
confidence: 56%
See 1 more Smart Citation
“…The expression of these selenoproteins is decreased in obese individuals due to their lower Se status (178). In COVID-19, selenoprotein expression may also be reduced by inflammatory factors and suppressed immune status (179). Therefore, dietary Se supplementation may help alleviate the respiratory and inflammatory clinical symptoms in obese patients suffering from COVID-19.…”
Section: Seleniummentioning
confidence: 99%
“…Darüber hinaus waren die Se-Spiegel bei überlebenden Patienten, die wieder von der Intensivstation entlassen werden konnten, signifikant höher als bei den verstorbenen Patienten (Serum-Se ca. 53 vs. 41 µg/l) [21]. Basierend auf einem systematischen Review wurde zudem nahezu zeitgleich eine Stellungnahme der European Society for Clinical Nutrition and Metabolism (ESPEN) publiziert [22], die die Bestimmung von Mikronährstoffen bei Covid-19-Patienten empfiehlt, u. a. Vitamin D, Zink und Selen.…”
Section: Covid-19 Und Ein Blick Nach Vornunclassified